Essays on the economics of foreign aid in Niger - Pedrosa Garcia, Jose Antonio (School of Economics, 2018)
This thesis identifies the gaps in the literature on foreign aid, and tries to fill some of them focusing particularly on Niger, a country that has received aid since its independence in 1960, yet remains one of the world's poorest. The work contributes to the literature in three ways: First, it addresses moral hazard: the relationship between the International Monetary Fund (IMF) and the country is analysed through a historical case study. Niger's requests for assistance are accompanied by promises to undertake reforms; however, once aid is disbursed, these undertakings rarely materialize. Despite this record of poor (and deteriorating) compliance, IMF aid continues to flow, engendering perverse incentives and moral hazard. Secondly, it analyses whether aid is associated with poverty reduction. Aid is correlated with poverty, which is to be expected due to its pro-poor targeting nature. However, this study found increases in poverty associated with communities which were recipients of aid. To shed more light on this, households receiving aid were compared with those receiving no project assistance at all, and with households who benefited from non-aid based development projects. The results showed that changes in poverty levels among aid recipient households were not statistically different to those among households receiving no assistance. However, households benefiting from aid under-performed those who benefited from other projects. Thirdly, it explores whether aid brings utility to households through the provision of public goods. The results suggest that aid projects do help households. However, other sources of development projects are more efficient at doing so. Information is the key: it is a vital prerequisite for projects to address the needs of the population, and not all donors have the same information. Information can be obtained through co-funding projects with other donors, although there are also coordination costs. The models estimated allow the prediction of the benefits a project could provide to a household. Such predictive abilities could allow policymakers to coordinate donors' initiatives to maximize their effectiveness. However, at present Niger lacks the capacity to achieve such coordination. Furthermore, such an approach would involve having to reduce the least efficient donors to mere providers of finance (i.e. channel their resources through other donor types), a role they might not be willing to accept.